2017
DOI: 10.1167/17.5.7
|View full text |Cite
|
Sign up to set email alerts
|

Visual wetness perception based on image color statistics

Abstract: Color vision provides humans and animals with the abilities to discriminate colors based on the wavelength composition of light and to determine the location and identity of objects of interest in cluttered scenes (e.g., ripe fruit among foliage). However, we argue that color vision can inform us about much more than color alone. Since a trichromatic image carries more information about the optical properties of a scene than a monochromatic image does, color can help us recognize complex material qualities. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 39 publications
(38 reference statements)
3
38
0
Order By: Relevance
“…The fact that people can infer the original color of bleached surfaces indicates that they can identify the chromatic changes because of the bleaching process and to some extent discount them. This is consistent with the finding that people use chromatic cues (i.e., color saturation) to perceive a surface as wet (Sawayama et al, 2017). Because the changes are interpreted as a change in the state of the material, rather than a change in the material itself, it suggests that the visual system can somehow separate the saturation increase that is owing to wetting from the intrinsic color of the surface.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The fact that people can infer the original color of bleached surfaces indicates that they can identify the chromatic changes because of the bleaching process and to some extent discount them. This is consistent with the finding that people use chromatic cues (i.e., color saturation) to perceive a surface as wet (Sawayama et al, 2017). Because the changes are interpreted as a change in the state of the material, rather than a change in the material itself, it suggests that the visual system can somehow separate the saturation increase that is owing to wetting from the intrinsic color of the surface.…”
Section: Discussionsupporting
confidence: 84%
“…There has been very little research on the perceptions of transformations that affect color. Sawayama and colleagues (Sawayama, Adelson, & Nishida, 2017) found that modifying the color distributions of photographs of natural textures can alter whether they appear to be wet or dry. Specifically, enhancing chromatic saturation while increasing darkness and glossiness tended to make dry scenes look wet.…”
Section: Introductionmentioning
confidence: 99%
“…Flours were brighter when processed at 11% moisture, at 102 m/s, and at small screen aperture, though differences in brightness due to seed moisture were of small practical significance (Table ). In general, flour with higher water content is expected to reflect less light and appear darker than the same flour at lower water content (Sawayama, Adelson, & Nishida, ). However, lower brightness values were observed at lower moisture content.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, we used only eight mixtures of dough as experimental stimuli, which limits the generalizability of our findings, because it is unclear whether the findings can be applied to materials other than dough. Sawayama et al (2017) demonstrated that the surface color of wet objects looks more saturated, which suggests that perceptible cues of moisture might depend on the type of material. Furthermore, the number of stimuli used in these two experiments was small, which makes it difficult to conclude if the results reflect the general characteristics of dough or characteristics specific to the stimuli.…”
Section: Discussionmentioning
confidence: 99%